2018
DOI: 10.1021/acs.est.8b00946
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photocatalytic Degradation Performance by Fluid-Induced Piezoelectric Field

Abstract: The introduction of a piezoelectric field has been proven a promising method to enhance photocatalytic activity by preventing photoelectron-hole recombination. However, the formation of a piezoelectric field requires additional mechanical force or high-frequency ultrasonic baths, which limits its potential application on industrial scale. Therefore, it is of great practical significance to design the catalyst that can harvest the discrete energy such as the fluid mechanical energy to form the electric field. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(73 citation statements)
references
References 41 publications
2
71
0
Order By: Relevance
“…the degradation rate of Rhodamine B (RhB) over spherical lead zirconate titanate (PZT) was improved ( Figure 3c,d), [66] and the monitored reactive oxygen species (ROS) indicated that the shearing force during the stirring process was well utilized by catalysts. [19] Piezocatalytic materials with hierarchical structure will be more efficient for capturing the fluid mechanical energy.…”
Section: Vortex-induced Shearing Forcementioning
confidence: 99%
“…the degradation rate of Rhodamine B (RhB) over spherical lead zirconate titanate (PZT) was improved ( Figure 3c,d), [66] and the monitored reactive oxygen species (ROS) indicated that the shearing force during the stirring process was well utilized by catalysts. [19] Piezocatalytic materials with hierarchical structure will be more efficient for capturing the fluid mechanical energy.…”
Section: Vortex-induced Shearing Forcementioning
confidence: 99%
“…Photocatalytic technology has attracted increasing attention not only for its simplicity and convenience, but also for its direct uti-lization of sunlight recently [18][19][20][21]. Research on photocatalytic reduction of Cr(VI) is becoming much more extensive [22,23], among which TiO 2 is the most commonly used photocatalyst [24].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with various traditional techniques, photocatalytic degradation can be carried out under ambient conditions, with complete degradation of organic pollutants into CO 2 and H 2 O . Among all the photocatalysts, TiO 2 has received the increasing attention since photocatalytic water splitting was studied, because of its low cost, nontoxicity, wide band gap, and chemical and light stability . However, TiO 2 has a wide band gap of 3.2 eV, which can only absorb UV light ( λ < 387 nm) and restricted the full absorption of sunlight (only 3%‐5%) …”
Section: Introductionmentioning
confidence: 99%